Refractory Temporomandibular Joint Dislocation – Reduction Using the Wrist Pivot Method - Vincent W.M. Lum; Juliana Poh (Clinical Practice and Cases in Emergency Medicine, 2017)
We report a case of a 19-year-old male who presented to the emergency department with refractory atraumatic temporomandibular joint dislocation. Multiple attempts at reduction by emergency physicians before and after sedation were unsuccessful. The dislocation was eventually reduced using the wrist pivot technique. This case highlights the need to consider alternative methods of temporomandibular joint reduction, particularly in cases refractory to reduction despite the use of sedation.